The Relationship between Exposure to Lead-Containing Welding Fumes and the Levels of Reproductive Hormones - Somayeh Farhang Dehghan; Younes Mehrifar; Arash Ardalan (Ubiquity Press, 2019)
Background: Inhalation of lead oxide fumes may cause lead poisoning. Lead has been proven to have harmful effects on different organs. This study aimed to investigate the relationship between the concentration of lead fumes and the levels of reproductive hormones among exposed welders. Methods: A total number of 165 individuals of a construction industry of water pipelines, including 85 welders as the exposure group and 80 administrative staff as the non-exposure group were selected for study. The National Institute for Occupational Safety and Health (NIOSH) 7300 method was used for the purpose of sampling and analysis of lead fumes. Likewise, the NIOSH 8003 method was employed to determine the blood lead level. The level of luteinizing hormone (LH), follicle-stimulating hormone (FSH), and testosterone were measured by Chemiluminescence immunoassay(CLIA) test. Data analyses were done by SPSS ver.21 using descriptive statistics, Student›s t-test and Spearman›s correlation test. Results: The average concentration of lead fumes in the breathing zone and blood were 0.57 ± 0.12 mg/m3 and 460.28 ± 93.65 μg/L, correspondingly, which both were significantly higher than threshold limit values (TLV) and biological exposure index (BEI) recommended by American Conference of Governmental Industrial Hygienists (ACGIH)(P < 0.05). The mean levels of LH and FSH were higher in the exposed group than those in the control group (P < 0.05), however, the mean levels of testosterone were lower in the exposed group compared to non-exposed ones (P < 0.05). A strong correlation was found between the concentration of lead fumes and the blood lead levels (r = 0.82; P = 0.003). Blood lead levels were inversely related to the testosterone levels and directly related to LH (r = 0.72; P = 0.004) and FSH (r = 0.78; P = 0.001) levels. Conclusions: Occupational exposure to metal fumes containing lead among welders may alter the level of sexual hormones and potentially harm the reproductive system.